PERBANDINGAN CRUNCH FREE ABS DENGAN ABDOMINAL EXERCISE KOMBINASI BRACING DALAM MENGURANGI DIASTASIS RECTI PADA POSTNATAL PERVAGINAM (Lembaga Penerbitan Universitas Esa Unggul, 2022)
AbstractDiastasis recti is often characterized by a prominent midline following increased intra-abdominal pressure, thinning and widening of the linea alba, coupled with weakness of the abdominal wall muscles. Diastasis recti bise causes complications such as pelvic floor muscle dysfunction, umbilical hernia, incontinence, and prolapse of the uterus. To return the abdominal muscles to normal again, crunch free abs exercises or andominal exercises combined with bracing can be done. This study aims to determine the comparison of crunch free abs with abdominal exercises combined with bracing in reducing diastasis recti in postnatal vaginal delivery. This study used a quasi-experimental design with a pretest – posttest design. The sample was divided into two groups, group A was given the crunch free abs treatment and group B was given the combination bracing abdominal exercise treatment. Based on the results of statistical tests with Mann Whitney obtained a significance result of 0.747 (> 0.05) so that it can guarantee that there is no difference in the effect of crunch free abs with abdominal exercises on the reduction of rectal diastasis in postnatal vaginal women.Keyword : abdominal exercise, crunch free abs, diastasis rectiAbstrakDiastasis recti sering ditandai dengan garis tengah yang menonjol mengikuti peningkatan tekanan pada intra abdomen, penipisan dan pelebaran dari linea alba, ditambah dengan kelemahan otot – otot dinding perut. Diastasis recti bise menyebabkan komplikasi seperti disfungsi otot dasar panggu, hernia umbilicus, inkontinensia, dan prolaps urteri. Untuk mengembalikan otot abdomen menjadi normal kembali bisa dilakukan latihan crunch free abs atau andominal exercise kombinasi bracing. Penelitian ini bertujuan untuk mengetahui perbandingan crunch free abs dengan abdominal exercise kombinasi bracing dalam mengurangi diastasis recti pada postnatal pervaginam. Penelitian ini menggunakan desain quasi eksperimental dengan pretest – postest design. Sampel dibagi menjadi dua kelompok, kelompok A diberikan perlakuan crunch free abs dan kelompk B diberi perlakuan abdominal exercise kombinasi bracing. Berdasarkan hasil uji statistik dengan uji Mann Whitney didapatkan hasil signifikansi 0.747 (>0.05) sehingga dapat disimpulkan tidak ada perbedaan pengaruh antara crunch free abs dengan abdominal exercise terhadap penurunan diastasis recti pada wanita postnatal pervaginam.Kata Kunci : abdominal exercise, crunch free abs, diastasis recti